Prevalence of Malaria Parasitemia (MP) and Hepatitis B Surface Antigen (HBsAg) Co-Infection Among HIV/AIDS Patients, Jalingo, Taraba State - Y., Akwa Vera; Patricia, Okonofua Eghe; Daniel, Ifraimu; David, Bando Christopher; Haruna, David Ephraim; Nashuka, Adamu Tutuwa (Darul Yasin Al Sys, 2024)
Human Immunodeficiency Virus (HIV) cannot be called a particular diseases or infection, but it could rightly be referred to as a phenomenon or syndrome that breaks through the body defense mechanism gradually which exposes the body to all kind of diseases resulting in Acquired Immune Deficiency Syndrome (AIDS). This Study focused on the prevalence of malaria and Hepatitis B surface Antigen (HBsAg) in people living with HIV. The result of the study has revealed that out of 148 HIV patients attending clinic at government house clinic Jalingo, 114 (77%) tested positive for malaria and 13 tested positive to hepatitis B surface antigen (HBsAg) with a prevalence of 8.8%. An association between HIV and occupation was evaluated, high risk occupation, based on the exposure to associated risk factor (student, civil servants and business men) accounted for high prevalence of 75.6%, while low risk occupation (housewives and farmers) accounted for 24.5%. 91(61.4%) of the patients reside in the rural areas while 57(38.5%) reside in the urban area. It was observed that male of both rural and urban area within the age group of 26-30 and 41-45 years presented a higher prevalence of 39% and 18.2% respectively while patients of both rural and urban area within the age group of 0-5 and 11-15 years accounted for a lower incidence rate with only 2.4% and 4% respectively.